Evaluation of the Effectiveness of the Preliminary Chemical Treatment of Grape Cake and Environmental Aspects of the Chemical Hydrolysis Process - Jamalov Zohid Zafarovich; Kemalov Ruslan Alimovich; Islamov Sahib Yakhshibekovich (Genius Journals, 2023)
During operation, grape cake is pretreated with nitric acid before preparation for the process of enzymatic hydrolysis. When producing biofuels of the second generation, agricultural waste, industrial and forestry waste containing lignin cellulose are mainly used. Chemical processing of raw materials ensures fast and efficient flow of the enzymatic hydrolysis process. In order to avoid harm to the environment and ecology during chemical treatment, the solution used is repeatedly used and at the end of the experiment is neutralized with ammonia
Keywords: grape cake; hydrolysis; temperature